2021
DOI: 10.4085/1062-6050-447-20
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Injuries in National Collegiate Athletic Association Men's Football: 2014–2015 Through 2018–2019

Abstract: Context Football is among the most popular collegiate sports in the United States, and participation in National Collegiate Athletic Association (NCAA) football has risen in recent years. Background Continued monitoring of football injuries is important for capturing the evolving burden of injuries in NCAA football. The purpose of this study was to describe the epidemiology of football-related injuries among men's NCAA footba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
14
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 15 publications
2
14
0
1
Order By: Relevance
“…A recent report found that basketball, soccer and football had the highest ankle sprain rates, with football showing the largest proportion of ankle sprains overall 4 . Regarding football, participation in National Collegiate Athletic Association (NCAA) football remains popular and continues to rise annually 5 . Between 2015 and 2018 ankle injuries were among the largest proportion (12.5%) of all injuries reported at all levels of collegiate football, including lateral ankle sprains (LAS) at 6.9% of injuries 5 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent report found that basketball, soccer and football had the highest ankle sprain rates, with football showing the largest proportion of ankle sprains overall 4 . Regarding football, participation in National Collegiate Athletic Association (NCAA) football remains popular and continues to rise annually 5 . Between 2015 and 2018 ankle injuries were among the largest proportion (12.5%) of all injuries reported at all levels of collegiate football, including lateral ankle sprains (LAS) at 6.9% of injuries 5 .…”
Section: Introductionmentioning
confidence: 99%
“…Regarding football, participation in National Collegiate Athletic Association (NCAA) football remains popular and continues to rise annually 5 . Between 2015 and 2018 ankle injuries were among the largest proportion (12.5%) of all injuries reported at all levels of collegiate football, including lateral ankle sprains (LAS) at 6.9% of injuries 5 . As participation in football and other sports continues to rise the prevalence of ankle injuries would be expected to increase as well supporting the need to identify potential strategies for reducing such injuries.…”
Section: Introductionmentioning
confidence: 99%
“…Lateral ligament complex tears (or lateral ankle sprains) have been reported to account for most sports-related ankle sprains. 13 Previous studies have shown ankle sprains to be a prevalent injury among athletes participating in National Collegiate Athletic Association (NCAA) competition, [5][6][7]24,27 and recent evidence suggests that lateral ankle sprains are common injuries across field-and court-based NCAA sports. 34 Although injury prevention efforts that include balance and proprioceptive training have been shown to be effective in mitigating the risk of ankle sprain in different settings, 2,10,35 advances in prevention efforts depend on routine and systematic epidemiological investigations aimed at capturing the burden of this injury in various athlete populations.…”
mentioning
confidence: 99%
“…34 However, the most recent investigation of lateral ankle sprains among NCAA athletes spanned the 2009-10 through 2014-15 academic years. 34 Given recent evidence indicating a high prevalence of this injury in various NCAA sports, [5][6][7]24,27 it remains critical to appraise the evolving burden of this injury among NCAA athletes. Accordingly, the purpose of this study was to characterize the epidemiology of lateral ligament complex tears in NCAA men's and women's sports during the 2014-15 through 2018-19 academic years.…”
mentioning
confidence: 99%
“… 20 Concussion is the leading cause of injury in NCAA football players, accounting for 7.5% of football injuries. 5 These injuries most commonly occurred while blocking (20.4%) or tackling (19.9%). 20 Emphasis and formal rules have been placed on removing unnecessary contact to the head and neck area during these activities in order to reduce the incidence of concussion.…”
mentioning
confidence: 99%